PES PLANUS PLANTARIS TERHADAP STABILITAS POSTURAL VERTICAL-JUMP MELALUI POSTURAL SWAY ATLET BASKET - Primal, Def (Indonesian Journal of Nursing Health Science, 2018)
Pes planus plantaris incident will increase plantar pressure because of body weight resistance during activities. Overuse activity is at risk of injury to the lower limb and will decrease curvature in the plantar arch. Basketball athletes with continuous weight-bearing exercise activity will affect the curvature of the plantar, causing the malformation of the foot arch to become flatter (flatfoot). This condition is reported to affect postural stability during the move. This is quantitative cross-sectional analytics study from basketball athletes involved 47 subjects. Subjects foot arch type determined with graph paper footprint. AMTI Accupower Force flatform posturography (force plate) determine athletes postural stability. Examination were performed in dynamic vertical jump (basketball primary moves) to determine the postural sway diameter of CoP. It revealed that 80,9% of subjects had flat plantar arch (pes planus plantaris). Basketball athletes have tendency having postural sway disturbance. The mean value of the postural sway diameter of CoP on subject with pes planus plantaris have significant correlation on the postural stability.Pes planus plantaris is affected by the length and the intensity of the exercise. This condition will significantly affect postural stability dynamic vertical motion (vertical jump).Â Keywords: dynamic stability, footprint, postural stability